The Implementation of Literacy and Numeracy in the Kampus Mengajar Program - Dhaksietsatsura, Virzha Aulianna; Arini, Ira; Fajarwati, Ayu (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
Kampus Mengajar is a government program that provides opportunities for university students to engage in off-campus learning for one semester by becoming partners of teachers in innovating creative and innovative learning strategies and models in targeted schools. These schools are generally identified as having low scores on the Minimum Competency Assessment (Asesmen Kompetensi Minimum/AKM). This study aims to describe the implementation of literacy and numeracy programs within Kampus Mengajar. A qualitative descriptive approach was employed, with data analysis conducted using the Miles and Huberman model. The research subjects were fifth-grade students from two elementary schools in Lebak Regency, Banten. Data were collected through observation, interviews, documentation, and field notes. The findings indicate that the Kampus Mengajar program benefits students, teachers, lecturers, and schools, particularly in improving students"™ literacy and numeracy AKM scores compared to the previous year. Furthermore, the program highlights the need for continued mentoring, especially for students with special needs and those who still face difficulties in reading and arithmetic.